Spiritualitas Kepemimpinan Kaum Awam dalam Gereja Sinodal - Nerius Seto; Mutiara Andalas (Fakultas Teologi, Universitas Sanata Dharma, 2025)
In order for a Synodal Church to be realized, laypeople are essential. All members must actively participate in walking together, but especially the laity, who are crucial to the establishment of a synodal church. The challenge in aiming for a synodal church is the absence of lay participation. This is because of the laity's ignorance of their role in establishing a synodal church, their perception of the church as hierarchical, and their lack of comprehension of spirituality in ministry. According to Christophe Pierre (2021),